Case Report: Extraskeletal osteosarcoma with preceding myositis ossificans - Imada, Hiroki; Torigoe, Tomoaki; Yazawa, Yasuo; Kanno, Satoshi; Ichikawa, Jiro; Yamaguchi, Takehiko; Kawasaki, Tomonori (Frontiers in Oncology, 2023)
Extraskeletal osteosarcoma (EO) is a soft tissue sarcoma characterized by the production of bone matrix by neoplastic cells. Benign osteoid in EO, leading to a diagnostic dilemma, is rarely encountered. Herein, for the first time, we present a case with cytogenetically confirmed EO combined with or preceding myositis ossificans (MO). A 21-year-old man had a mildly painful swelling in his left knee. Imaging studies demonstrated a 39-mm mass with peripheral mineralization and cystic change on the posterolateral side of the left fibular head. He was clinically suspected of having either MO or a malignancy, such that wide resection was performed. Macroscopically, the mass was grayish to brown. In the cut section, multiple cystic lesions in addition to solid components were noted. Histopathologically, the solid components demonstrated diffuse proliferation of pleomorphic tumor cells with osteoclast-like giant cells. The malignant tumor cells formed osteoid. In the periphery, the mass was benign, showing mature bone tissue and focally non-malignant woven bone with fibroblasts, compatible with zonation. Fluorescence in situ hybridization (FISH) demonstrated split signals of the USP6 gene. These findings suggested EO with preceding MO. Although the pathogenesis remains to be elucidated, the observed USP6 rearrangement might contribute to both the diagnosis of EO with preceding MO and an understanding of the underlying histopathology.